2006
DOI: 10.1128/aac.50.1.237-242.2006
|View full text |Cite
|
Sign up to set email alerts
|

Activity of a New Oral Streptogramin, XRP2868, against Gram-Positive Cocci Harboring Various Mechanisms of Resistance to Streptogramins

Abstract: The antibacterial activity of XRP2868, a new oral streptogramin composed of a combination of RPR132552 (streptogramin A) and RPR202868 (streptogramin B), was evaluated against a collection of clinical grampositive isolates with characterized phenotypes and genotypes of streptogramin resistance. The effects of genes for resistance to streptogramin A or B on the activity of XRP2868 and its components were also tested by cloning these genes individually or in various combinations in gram-positive recipient strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
3
13
0
Order By: Relevance
“…Previous studies have shown that NXL 103 inhibits staphylococci, S. pneumoniae, nonpneumococcal streptococci, H. influenzae, and anaerobes at Յ1 g/ml. NXL 103 is approximately 4 times as potent as quinupristin-dalfopristin against S. aureus, Enterococcus faecium, streptococci, and H. influenzae (7,8,14,16). Our MIC results reflect those published previously by both us and others.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Previous studies have shown that NXL 103 inhibits staphylococci, S. pneumoniae, nonpneumococcal streptococci, H. influenzae, and anaerobes at Յ1 g/ml. NXL 103 is approximately 4 times as potent as quinupristin-dalfopristin against S. aureus, Enterococcus faecium, streptococci, and H. influenzae (7,8,14,16). Our MIC results reflect those published previously by both us and others.…”
supporting
confidence: 81%
“…Rapid kill kinetics against all of the strains tested, with the exception of MRSA, adds to the attractive properties of NXL 103. Quinupristin-dalfopristin has been described as often being bacteriostatic against MRSA, possibly mediated by constitutive erm(B) production by most MRSA strains (7,8,14,16). This was reflected in the results obtained with NXL 103.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Rapid hydrolysis of the diethylaminoethylsulfonyl group at a physiological pH converts dalfopristin to virginiamycin M (11). In vitro studies have shown that the streptogramin A flopristin in NXL 103 has higher antimicrobial activity than that of its counterpart in Synercid, dalfopristin, suggesting that the increased activity of NXL 103 is mainly due to flopristin (6,7). The streptogramin B component quinupristin of Synercid carries a quinuclidinylthiomethyl group compared to a methylmorpholine group in linopristin of NXL 103 (Fig.…”
mentioning
confidence: 99%
“…To overcome venous irritation caused by Synercid, and in order to reduce health care costs, a new and orally available streptogramin combination, flopristin-linopristin (NXL 103), a 70:30 (wt/wt) mixture of flopristin to linopristin, has been developed for use in the outpatient setting. NXL 103 has been shown to be more effective than Synercid in treating a large number of Gram-positive bacteria and their clinical isolates (6)(7)(8)(9) and also has the potential to become an important drug in the treatment of community-acquired pneumonia and complex skin and soft tissue infections, including MRSA (10).…”
mentioning
confidence: 99%